Pekerjaan Sosial Sebagai Disiplin Ilmu dan Profesi - Adi Fahrudin (2018)
Social work is an academic discipline and practice -based profession. As an academic discipline, social work is supported by theories derived from social work itself, social sciences and other relevant sciences. This confirm that social work is an applied social science that is at once a profession. To be considered a profession that social work should be practiced. Therefore, social work not only studied as an academic discipline but must be practiced. Practice without based on academic disciplines not directed and could be fraudulent, academic disciplines without practice is nothing more than discourse.